Testing for cultural measurement equivalence in research on domestic and international tertiary students' fear of crime - Xiong, Lin (The Australian and New Zealand journal of criminology, 2017)
ObjectivesEducation institutions routinely instruct students on how to remain safe from crime. We hold that this instruction and much of the associated practice might be problematic, because none of the researchers who have contrasted the fears and the victimization avoidance strategies of domestic and international students have tested for cultural measurement equivalence. This study aims to examine, whether cultural measurement equivalence exists when domestic and international tertiary students respond to fear of crime-related measures.MethodsThis cross-sectional study involved 1170 tertiary students across four Melbourne-based universities, Australia. Multiple group confirmatory factor analyses with covariance and mean structures, using structural equation modeling, were used to test whether the same constructs were measured across international and local tertiary students.ResultsThe two cohorts hold the same conceptual frame of reference when responding to the measurement items. However, the cohorts display different true score values in relation to a number of questionnaire items associated with fear of crime, perceptions of safety, and avoidance behavior.ConclusionsThis study suggests that researchers need to render testing for cultural measurement equivalence standard practice, when undertaking cross-cultural studies of student safety and that such practice should also be incorporated into student safety programs.